Hypertension in men - An emerging public health challenge for India: Evidence from national family health survey-4 - Prasad Waingankar; Sneha Kotian; Noopur Kulkarni; Palanivel Chinnakali; Mahendra Pratap Singh; Sonu Goel (Wolters Kluwer Medknow Publications, 2023)
Background: Men in the 25-54 year age group form the major workforce in developing countries like India. The rising trend of hypertension in this age group is a growing matter of concern. Objectives: This study analyzed secondary data analysis from the National Family Health Survey-4. Methods: Men in the 25-54 age group (n = 76,410) from 640 districts of the country were included in the study. State and district-wise trends in hypertension in men along with selected individual lifestyle characteristics were displayed using a geographic information system. Results: The prevalence of hypertension among men in the age group of 25-54 was found to be 35.6% for the entire country. In urban India, the prevalence of hypertension was 38.4% (uncorrected - 40.2%) compared with 33.8% (uncorrected - 34.9%) in rural India. Among the 27,973 hypertensives, 6984 (25%) were the known hypertensives prior to the survey. Out of these only 2403 (34.4%) were taking medicines. The prevalence of tobacco use in any form among the men in this age group was 45.7% (uncorrected - 49%). Conclusion: In conclusion, the study highlights the burden of hypertension in men in the prime age group along with the alarming burden of tobacco consumption and recommends public health and policy interventions targeting both hypertension and tobacco control. It requires urgent attention and specialized strategies in tiding over this epidemic brewing in the workforce of the country.